Loss of smell in lung cancer patients undergoing chemotherapy: Prevalence and relationship with food habit changes. (March 2023) - Drareni, K.; Dougkas, A.; Giboreau, A.; Laville, M.; Souquet, P.J.; Nazare, J.A.; Fournel, P.; Bensafi, M.
Highlights: Half of the patients' group exhibited hyposmia before the begining of chemotherapy. Patients had lower odor detection and identification abilities compared to controls. Food odors were perceived as less edible by patients compared to controls. Patients with hyposmia declared using more condiments than patients without hyposmia. Abstract: Background and Objectives: Cancer patients undergoing cytotoxic chemotherapies exhibit a series of adverse side effects including smell and taste alterations, which can have a significant impact on their food behavior and quality of life. Particularly, olfactory alterations are often underestimated, although declared as frequent by cancer patients. In the present study, we set out to examine loss of smell in lung cancer patients undergoing chemotherapy and its relationship to food habits. Material and Methods: Forty-four bronchial cancer patients receiving cisplatin and 44 controls age and gender matched participants were tested for olfactory and gustatory functions using the European Test of Olfactory Capabilities and the Taste Strips test. Participants reported their food and dietary habits by filling a self-administered questionnaire. Patients were tested under two different sessions: i) before the beginning of the treatment, and ii) 6 weeks later, after 2 cycles of chemotherapy. Controls were tested under the same protocol with two sessions separated by 6 weeks. Results and Conclusions: The results highlighted decreased smell and taste abilities in almost half of the lung patients' group even before the exposition to Cisplatin. On a perceptual level, patients rated typical food odors as less edible compared to controls. Moreover, within the patients' group, hyposmics reported using more condiments, possibly as a compensatory mechanism to their decreased sensory abilities. Taken together, these findings showed that loss of smell is prevalent in lung cancer patients and is related to changes in dietary practices including seasoning. Future studies will provide a better understanding of these sensory compensation mechanisms associated with olfactory loss and their effects on food pleasure in this patient population.